Effects of 48-hour feed deprivation on acute-phase response in horses - Di Filippo, Paula Alessandra; Duarte, Bárbara Ribeiro; Albernaz, Antônio Peixoto; da Fonseca, Leandro Abreu; Viana, Inácio Silva [UNESP]; Quirino, Célia Raquel (FapUNIFESP (SciELO), 2022)
The objective of this study was to evaluate the effect of feed restriction on acute-phase response in horses. Twenty horses were deprived of food for 48 h and others 12 animals (control) had free access to water and hay. They were closely monitored and examined, and blood samples were taken at the beginning (0) of the study and 6, 12, 18, 24, 30, 36, 42 and 48 hours afterward. Data were submitted to two-way analysis of variance with repeated measures and statistical significance was P ≤ 0.05. The horses tolerated feed restriction without serious clinical complications. Feed restriction induced an increase in the acute-phase response by elevating serum concentrations of α2-macroglobulin (24-38 h), ceruloplasmin (36-48 h), α1-antitrypsin (30-48 h), α1-acid glycoprotein (42-48 h) and haptoglobin (42-48 h). Nutrient deprivation raised the levels of circulating cortisol, which acts on the innate immune system, which then induces the acute-phase response. In conclusion, food restriction is a physical stressor for horses, capable of inducing an acute-phase protein reaction, characterized by increased production of α2-macroglobulin, ceruloplasmin, α1-antitrypsin, α1-acid glycoprotein and haptoglobin.
Efeitos da privação alimentar de 48 horas na resposta de fase aguda em cavalos
Keywords: Equine; Feed restriction; Immune response; Inflammation; Proteins; Stress